2016
DOI: 10.1002/jso.24134
|View full text |Cite
|
Sign up to set email alerts
|

The importance of margins in head and neck cancer

Abstract: An estimated 200,000 deaths each year worldwide are due to cancer of the head and neck, mostly mucosal squamous cell carcinoma and nonmelanoma skin cancer. The status of surgical margins is important for prognosis and need for adjuvant therapy. We will discuss how margin status impacts outcomes and therapy, and the conundrum of determining margin status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 102 publications
(173 reference statements)
0
47
0
Order By: Relevance
“…1 This risk is estimated based on clinicopathological features and directly impacts management decisions. [4][5][6][7][8][9] In contrast, the importance of microscopic positive margins is well recognized in many other malignancies, including head and neck squamous cell carcinoma, 10 melanoma 11 and breast cancer. 2 Although grossly positive tumour margins are known to be predictive of poor outcome in PTC, 3 the impact of microscopic positive margins is less clear.…”
Section: Introductionmentioning
confidence: 99%
“…1 This risk is estimated based on clinicopathological features and directly impacts management decisions. [4][5][6][7][8][9] In contrast, the importance of microscopic positive margins is well recognized in many other malignancies, including head and neck squamous cell carcinoma, 10 melanoma 11 and breast cancer. 2 Although grossly positive tumour margins are known to be predictive of poor outcome in PTC, 3 the impact of microscopic positive margins is less clear.…”
Section: Introductionmentioning
confidence: 99%
“…18 Local recurrence is not only a result of the mere persistence of cancer cells in the surgical field, but also results from their increased survival chances in a postsurgical environment marked by abundant growth factors and increased delivery of oxygen and nutrients. 19 Postsurgical persistence of cancer cells may also be an indirect reflection of aggressive tumor biology, as it is frequently associated with high-stage tumors, perineural invasion, infiltrative tumor margins, and other highrisk factors that decrease chances for successful surgical resection.…”
Section: Marginsmentioning
confidence: 99%
“…18,19,21 Not surprisingly, local recurrence is sharply increased in the setting of positive margins, but also in patients with close surgical margins the rate of local recurrence is increased, albeit to a lesser degree. As a reflection of adverse tumor biology, several studies also confirm disease-specific survival (DSS) and overall survival to be influenced by close and positive surgical margins.…”
Section: Marginsmentioning
confidence: 99%
“…1 The safest margin for surgical resection of oral cancer is typically considered 5 mm from the permanent edge of the tumor. 2 Recently, the definition of a negative margin was proposed to 2.2 mm, decreasing from the previous standard of 5 mm for the oral tongue. 3 Another study found cuts within 1 mm of oral cavity SCCa tumor margins are associated with significantly increased recurrence rates.…”
Section: Introductionmentioning
confidence: 99%